E-APPS: a digital platform for application processing and records management in private educational institutions with data visualization - Eusebio Laureta Mique Jr.; Alvin Reyes Malicdem; Liezl Padilla Mique; Marylen De Guia Rodriguez; Marydel Carrera Estira (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Online application and processing systems are digital platforms that allow applications to be submitted, reviewed, and processed electronically. These systems enhance efficiency by streamlining workflows, reducing paperwork, and enabling faster and more accurate decision-making for both applicants and administrators. This paper presents the development, implementation, and evaluation of E-APPS: an electronic application processing system for private schools and educational institutions, and records management (E-APPS). Specifically, it determined the process and forms involved in private school applications for approval, developed an E-APPS for private schools and records management using the extreme programming model, assessed the software quality of the E-APPS, and evaluated its technical performance. Based on the result, the existing application process includes submission, validation of documents, inspection, endorsement to the regional Office, approval, and issuance of permits. The E-APPS was developed and evaluated to ensure it meets quality requirements. The developed system was also tested and proven to work reliably even when many users use it simultaneously. It can accommodate hundreds of users without delays or system errors.